Topical Issues of the National and Regional Innovation System Development - Pidorycheva, I.Yu. (Science and Innovation, 2024)
Features of innovation system formation at the national level have been described; role of the regional aspect in innovation processes has been defined. Historical experience of innovation system formation in the developed countries has been considered. The situation in the sphere of innovation system formation in Ukraine has been described. The national innovation system model has been offered to be based on the development of regional innovation systems using a holistic approach to their formation and support. The practical recommendations on the implementation of priority measures to promote the development of national and regional innovation systems in Ukraine have been given. The conditions for successful development of innovation systems have been formulated.